(untitled) (Scientific journal of the Fergana State University, 2023)
In the article, on the basis of archival documents, information from existing literature, the development of cotton cultivation in Andijan uezd of Fergana region during the rule of the Russian Empire and the emergence of cotton ginning and oil enterprises, their condition, technical equipment, volume of production, the condition of workers, wages paid to them, etc. analyzed.